Caught in the act: an anthology of performance art by Canadian women - Mars, Tanya; Householder, Johanna; Mars, Tanya; Householder, Johanna (YYZ Books, 2004)
This indispensable anthology gives readers access to an important and under-recognized subject in recent Canadian art history. Edited by two seminal Canadian performance artists, this book focuses on the 70s and 80s; a time when women made a big and noisy impact. Full of sass and insight, this essential collection is part survey, part critical discourse, and part reference book, containing five critical essays, thirty-four artist's profiles, and an extensive bibliography.
Keywords: 1900-1999; 1970-1979; 1980-1989; amériques; art contemporain; arts; canada; corps; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; régions géographiques; thématiques